Thermo-Fluid-Dynamics of a Ceramic Foam Solar Receiver: A Parametric Analysis. Issue 12 (3rd July 2020) - Andreozzi, Assunta; Bianco, Nicola; Iasiello, Marcello; Naso, Vincenzo
Abstract: The high efficiency of concentrated solar power (CSP) in energy conversion makes it a very attractive device for using solar energy as a substitute of nonrenewable energy sources. The open volumetric receiver plays an important role in the performance of a CSP. The optimized design of solar receiver implies the thorough knowledge of the heat transfer between the air and the foam and of the temperature distribution in the receiver. Heat transfer in the cylindrical SiC porous volumetric receiver of a solar tower, undergoing the impact of concentrated solar radiation, is investigated numerically in this paper. Governing equations are written with the volume averaging technique. A two-equation model for the energy equation, under the local thermal nonequilibrium assumption, is used. Numerical simulations are carried out through the commercial code COMSOL Multiphysics. The solid and fluid temperatures, the fluid velocity and the pressure drop, for various boundary and morphological conditions, are predicted and discussed. The receiver efficiency is finally maximized carrying out an extended parametric analysis of process parameters.